The Combined Use of the Temporoparietal Fascia Graft and Polycaprolactone Nasal Sheets in Iatrogenic Nasal Septal Perforation Repair - Yaşar, Murat (Springer Science and Business Media LLC, 2025)
Abstract Objective Medium- and large-sized iatrogenic nasal septal perforations are difficult to repair. Many techniques using local flaps with or without interposition grafts are used to repair septum perforation. The aim of this study was to describe our surgical technique for repairing iatrogenic nasal septal perforations with medium sized (1–2 cm) and large sized (> 2 cm). Methods We retrospectively reviewed 15 patients with medium- and large-sized iatrogenic nasal septal perforations treated with a sandwich technique (temporoparietal fascia and polycaprolactone nasal sheet as an interposition graft) by an endoscope-assisted intranasal approach at the Kastamonu Training and Research Hospital from September 2021 to September 2024. Clinical follow-up periods were between 3 and 28 months in duration (mean 12 months). Results Fifteen patients, nine men and six women, were operated on using this technique. A mean follow-up time is 12 months. Complete closure was achieved in 13 of 15 patients (86.6%). No complications were also occurred in either the early or late postoperative periods. Conclusion An endoscopic sandwich technique that uses a temporalis fascia polycaprolactone nasal sheet combined as an interpositioning graft to repair iatrogenic nasal septal perforations is described. The transnasal endoscopic sandwich technique for repairing of medium-sized and large-sized iatrogenic nasal septal perforations has a high success rate and is relatively easy to perform. Level of Evidence IV This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.